Development of Android-Based Class in Hole Teaching Materials to Increase Students' History Awareness - Nastiti Mufidah; Khoirun Nikmah; Tiksna Apta Samoda; Faninda Novika Pertiwi (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
Teaching materials are an important point in the implementation of student lectures in class. The availability of printed teaching materials is very unattractive in this modern era. This research aims to develop teaching materials for the Android-based Classical Indonesian History course. Research using ADDIE. Data collection techniques through pre-test and post-test for Tadris IPS students. The data analysis technique in this research went through three stages, namely expert validity test, normality test and paired sample t-Test. Android-based Classic Indonesian History with Mobile Learning (Class In Hole) teaching materials to increase students' historical awareness have an effect on increasing students' understanding of concepts based on the results of the